Effect of MoS2 addition on the wear mechanism of laser cladding AISI M2 coatings - Hao Ma; Peng Wang; Qingtao Guo; Jiayi He; Kuangxin Luo; Ning Wu; Fenghua Luo (Journal of Materials Research and Technology)
The AISI M2 coatings were prepared on H13 die steel substrates by laser cladding technology. The effects of MoS2 addition on the microstructure and wear resistance of the coatings were investigated. The results showed that adding MoS2 can reduce the wear rate of M2 coating, enhance the hardness of the coating, and affect the wear mechanism of the coating. The wear rate of the M2 coating is 3.33 × 10−5 mm3/N·m, mainly consisting of oxidative wear and abrasive wear. When the MoS2 addition reached 7 wt%, the wear rate is only 1.88 × 10−5 mm3/N·m, and the wear mechanism is mainly oxidative wear. The microstructure of the coatings was analyzed using X-ray diffraction techniques and scanning electron microscopy techniques, and its mechanism was thoroughly studied. MoS2 can refine grains and promote fine grain hardening. The average grain size of the M2 coating is 3.42 μm, but the average grain size of the coating containing 7 wt% MoS2 decreases to 1.40 μm.